The Use of translanguaging pedagogy in writing classes of Turkish EFL learners - KARABULUT, ASLIHAN (My University, 2022)
© 2022, Ozgen Korkmaz. All rights reserved.Despite the blurred boundaries among languages and classroom evidence contrary to the implementation of monolingual pedagogies, the dominance of monolingual policies for teaching foreign languages continues to persist. To provide foreign language learners with an appropriate bilingual pedagogy and target one of the most challenging second language (L2) skills, this study aimed to explore the role of translanguaging pedagogy (TP) in writing classes and participants’ perceptions regarding its implementation in English as a foreign language (EFL) context. The participants (n=63) at the English prep school of a state university were assigned as one control and two experimental groups. Throughout one semester, the first experimental group was exposed to TP in their writing classes, whereas the second one learned writing through the translanguaging instructional cycle excluding their mother tongue (L1). The control group had product-focused English-only writing classes. Quantitative data collected via four in-class writing tasks (WTs) from three groups were analysed using inferential statistics. A weekly questionnaire regarding the first experimental groups’ perceptions of TP was conducted. The results revealed significant gains in task achievement, lexical and grammatical range and accuracy, and cohesion and coherence favouring TP and the participants found the implementation of TP useful in helping them improve in a variety of aspects in their English writing classes.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sosyoloji; Eğitim; Social Sciences and Humanities; Psychology; Developmental Psychology; Sociology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, GELİŞTİRME; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, DEVELOPMENTAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Gelişim ve Eğitim Psikolojisi; Social Sciences & Humanities; Developmental and Educational Psychology; EFL; perception; Translanguaging; writing skill